Sources of Ionizing Radiation Used in Modern and Advanced NBC Reconnaissance Devices (Lecture) - E. V. Vasilkovsky; A. V. Dikun; I. G. Vasyukevich (Вестник войск РХБ защиты, 2022)
The lecture is intended to prepare students studying under an additional professional advanced training program for military specialists in radiation safety for all branches of the Armed Forces of the Russian Federation, as well as to train officials responsible for organizing and ensuring radiation safety in military units and organizations of the Ministry of Defense of the Russian Federation. The lecture addresses three educational questions: 1. Accounting and control of radiation sources in the system of state accounting and control of radioactive substances and radioactive waste. 2. General requirements for the operation of radiation sources. 3. Operation of sealed radionuclide sources as part of the technical means of the RCB for intelligence and control.